RADT-29. EFFECT OF RADIATION THERAPY ON OVERALL SURVIVAL FOLLOWING SUBTOTAL RESECTION OF ADULT PILOCYTIC ASTROCYTOMA. (9th November 2020) - Khalafallah, Adham; Jimenez, Adrian; Brem, Henry; Mukherjee, Debraj
Abstract: BACKGROUND: Pilocytic astrocytoma (PCA) is a low-grade glioma common in children but also rarely diagnosed in adults. The role of adjuvant radiation therapy (RT) in treating these tumors remains unclear. OBJECTIVE: We investigated the effect of RT on overall survival, specifically among adult patients who had undergone subtotal PCA resection. METHODS: Information on adult patients (age 18 years old) who had undergone subtotal PCA resection between 2004 and 2016 was collected from the National Cancer Database (NCDB). A multivariate Cox proportional hazards model was utilized to determine factors independently associated with overall survival. RESULTS: A total of 451 patients were identified. The mean age of our patient cohort was 36.8 years old, and the majority of patients (83.4%) did not receive radiation treatment following subtotal PCA resection. Overall median survival was 93.8 months. Survival was longer (p < 0.001) in the patients who did not receive post-surgical RT (median: 98.3 months) compared to patients who did (median: 54.8 months). Patients who had older age at diagnosis (hazard ratio [HR]=1.05, 95% confidence interval [CI]=1.03-1.07, p < 0.01), were Black or African American (HR=2.76, CI=1.12-6.46, p=0.019), received radiation during their initial treatment (HR=4.53, CI=2.08-9.89, p < 0.01), or had a Charlson/Deyo score of > 1 (HR=3.68, CI=1.55, p=0.003) had a significantly higher risk of death following subtotal PCA resection. CONCLUSION: Postoperative RT is independently associated with a significantly higher risk of death among adults who underwent subtotal PCA resection. Our findings provide a rationale for further investigation into the efficacy and safety of RT within this patient population.